Smart Contracts and Virtual Property Disputes in the International Metaverse Economy - salim; Arif; Junaidi Lubis; Chairus Suryati; Bambang Sutejo; Irma Herliza Rizki (Outline Publisher, 2025)
The rapid advancement of blockchain technology and the emergence of the metaverse as a cross-border digital economy have triggered new legal challenges, particularly concerning smart contracts and virtual property disputes. Smart contracts—self-executing agreements coded on blockchain—offer efficiency and transparency but raise critical questions about legal validity, jurisdiction, and dispute resolution when conflicts arise between parties from different countries. In the context of virtual ownership such as digital land, NFTs, and in-world assets, diverging national legal systems complicate the enforcement of rights over virtual property. This study analyzes how smart contracts are utilized in virtual property transactions and examines the evolving international legal approaches to disputes arising from such agreements. The research highlights the urgent need for an adaptive global legal framework, cross-jurisdictional recognition of digital rights, and the role of blockchain-based arbitration bodies as alternatives to traditional dispute resolution. It also explores the relevance of traditional contract law principles in decentralized virtual environments and the regulatory challenges related to digital identity and evidentiary standards. With a multidisciplinary approach, this abstract offers insights into the importance of legal harmonization and international collaboration in supporting a fair, predictable, and legally secure metaverse ecosystem.